Disabled women's knowledge of breast cancer and self examination: an educational strategy - França, Inacia Sátiro Xavier de; Oliveira, Cibely Freire de; Cruz, Giovanna Karinny Pereira; Coura, Alexsandro Silva; Enders, Bertha Cruz (Rev Rene, 2012)
The objective of the study was to identify the knowledge that physically disabled women have about breast cancer and self examination. An action research study with a non-probability sample composed of 15 women enrolled in the Association of Disabled Persons of the Compartment of Borborema, Campina Grande, PB, Brazil, using Questionnaires I and II, an educational folder, and a breast demonstration kit. This study was conducted in three stages: application of Questionnaire I; implementation of the educational intervention; and the post-intervention application of Questionnaire II. In the analysis of thematic content categories identified were: Disabled women’s needs for breast cancer information, beliefs and myths related to the origin of breast cancer, and self-care deficit related to the early detection of breast cancer. The educational activities enabled women to learn about breast cancer and to demonstrate interest in acquiring proactive attitudes for well-being.